Exploring the microbiota-gut-brain axis: impact on brain structure and function - Lidya K. Yassin; Mohammed M. Nakhal; Alreem Alderei; Afra Almehairbi; Ayishal B. Mydeen; Amal Akour; Mohammad I. K. Hamad (Frontiers in Neuroanatomy)
The microbiota-gut-brain axis (MGBA) plays a significant role in the maintenance of brain structure and function. The MGBA serves as a conduit between the CNS and the ENS, facilitating communication between the emotional and cognitive centers of the brain via diverse pathways. In the initial stages of this review, we will examine the way how MGBA affects neurogenesis, neuronal dendritic morphology, axonal myelination, microglia structure, brain blood barrier (BBB) structure and permeability, and synaptic structure. Furthermore, we will review the potential mechanistic pathways of neuroplasticity through MGBA influence. The short-chain fatty acids (SCFAs) play a pivotal role in the MGBA, where they can modify the BBB. We will therefore discuss how SCFAs can influence microglia, neuronal, and astrocyte function, as well as their role in brain disorders such as Alzheimer’s disease (AD), and Parkinson’s disease (PD). Subsequently, we will examine the technical strategies employed to study MGBA interactions, including using germ-free (GF) animals, probiotics, fecal microbiota transplantation (FMT), and antibiotics-induced dysbiosis. Finally, we will examine how particular bacterial strains can affect brain structure and function. By gaining a deeper understanding of the MGBA, it may be possible to facilitate research into microbial-based pharmacological interventions and therapeutic strategies for neurological diseases.